CARACTERÍSTICAS DE CARCAÇA DE OVINOS DAS RAÇAS SANTA INÊS E RABO LARGO SUBMETIDOS A DIETAS COM DIFERENTES PROPORÇÕES DE CONCENTRADO - LIMA, Hyanne Costa (2020)
The objective was to evaluate as quantitative characteristics, morphometric measurements, scores, technical composition and non-carcass components of lambs fed diets that include high or low concentrate proportions. Thirty-eight non-castrated males with a defined racial pattern were used: 19 Rabo Largo (16.68 kg ± 2.78 kg) and 19 Santa Inês (19.29 kg ± 3.28kg) animals. The treatments consisted of two diets, one of high concentrate (70%) and one of low concentrate (30%), with two sheep genotypes (Santa Inês and Rabo Largo), totaling four treatments. The design was in incomplete randomized blocks, in a 2 x 2 factorial scheme (two genotypes x two diets) and 10 repetitions per treatment. The experimental period lasted 52 days, being nine days of adaptation of animals to facilities, diets and management and 43 days for data collection. After the experimental period, the animals were fasted for solids for 16 hours and then slaughtered. The collected data were subjected to analysis of variance (F test) and the Tukey test with a 5% significance level was used to compare the means. For carcass parameters it was observed effect (P < 0.05) of diet and genotype for slaughter live weight, empty body weight, warm carcass weight, cold carcass weight and loin eye area, in which animals fed a diet containing high concentrate and Santa Inês breed presented the highest weights. The weights of the cuts: palette, rib leg and loin showed significant differences (P <0.05) for diet and genotype, with higher weights for Santa Inês lambs and for diets with high concentrate. Genotype and diet influenced (P < 0.05) the weights of the kidneys, rumen, small and large intestine, as well as the weights and yields of the spleen and liver. The size of the liver and spleen increased when the animals were fed a high concentrate diet, with Santa Inês sheep presenting higher weight in these organs. Effect (P <0.05) of interaction (genotypes x diets) on reticulum weight and yield was observed. The weight of the reticulum was lower (P <0.05) for Rabo Largo lambs fed a low concentrate diet, however, for this parameter, the value was similar to those obtained for Santa Inês sheep, regardless of the diet offered. The morphometric evaluations: croup perimeter, chest width, leg perimeter and chest depth were influenced (P < 0.05) by the high concentrate diet in favor of its higher energy level, indicating that this diet provided higher tissue deposition in relation to low concentrate diet. For tissue composition, diets and genotypes influenced (P < 0.05) the percentages of total fat and the muscle: bone and muscle: fat ratio. High concentrate diets provide higher carcass, cuts, viscera and fat weights in Santa Inês and Rabo Largo lambs. The use of the Santa Inês breed in confinement provides an increase in the weight of the carcasses, which presents greater weight of loin and leg, with greater muscle and muscle: fat ratio. Rabo Largo lambs have carcasses with greater fat deposition.